Agricultural Productivity and Poverty Alleviation in Nigeria - Umar, Aishat Princess; Rotimi, Mathew Ekundayo; Kolawole, Isiaka Olayinka (ABUAD Journal of Social and Management Sciences, 2023)
The study is designed to examine the relationship between agricultural productivity and poverty alleviation in Nigeria from 1981 to 2020. To achieve this objective, secondary data were collected on the relevant variables namely per capita income, which was used as a proxy for poverty, agricultural output, agricultural loans to individuals, and the real gross domestic product. The data used were sourced from the Central Bank of Nigeria (CBN) statistical bulletin and the World Bank database. The study adopted the Philips Perron test in testing for stationarity and the variables had a mixed order of integration. Auto Regressive Distributed Lag Model (ARDL) was adopted in carrying out the analyses after cointegration was established using the ARDL bounds test. The result of the study showed that an increase in agricultural output improved per capita income, which reduced the level of poverty. The model was also found to have no autocorrelation implying that the findings of the study are suitable for predictions and forecast. The study concluded that poverty can be alleviated through the improvement of the agricultural sector. The study also recommended among other things that the government should embark on policies that can strengthen the agricultural sector in Nigeria.